KEWENANGAN PENGADILAN MILITER UTAMA DALAM MELAKUKAN PENGAWASAN PERADILAN MILITER - Rifandhana, Raditya Feda (Jurnal Cakrawala Hukum, 2016)
The State of the Law is identical with the Unitary State of the Republic of Indonesia which has its basis in the RegulationsLegislation namely the 1945 Constitution of the State of the Republic of Indonesia, to the StateUnity of the Republic of Indonesia there are three famous teachings on tries political, namely the executive, legislative and judicative, each of which has authority over the supervision of each institution Unitary State of the Republic of Indonesia. The Judiciary has the supervisory authority on the judicial environment, in this case, is the military court environment which is the authority ofMain Military Court.